FORMATION OF STUDENTS' IDEOLOGICAL IMMUNITY BASED ON EDUCATIONAL CORRECTION ACTIVITIES - Bozorova Muattar Hamidovna (Scholar Express Journal, 2023)
In today's information era, it is necessary to pay attention to the tasks that need to be carried out in the formation of students' ideological immunity. The article deals with the formation of students' ideological immunity based on educational correctional activities
Keywords: ideological immunity; educational correction; student; information; technology